Penapisan Bakteri Termo-Amilolitik Dari Sumber Air Panas Sungai Medang, Kerinci, Jambi - Devi Syafriyani; Anthoni Agustien; - Periadnadi (Universitas Andalas, 2013)
This study aimed to observe the ability of isolated bacteria from Sungai Medang hot spring in producing amylase and to determine the activity and characteristic of isolated amylolytic bacteria which gave the highest amylolytic index. The water samples were collectied by using purposive sampling based on different level of temperatures. This study has successfully collected 48 bacterial isolated from the hot spring. To find the highest amylolytic activity, we tested ten isolated bacteria which have high amylolytic indices. We found that MV2.7 isolated from 740C of hot spring gave the highest amylolytic activity. The isolated bacteria was positive proteolytic, cellulolytic and negative lipolytic. The isolated bacteria showed higher and more spesific activity on rice starch rather than corn and sago starchKeywords: Screening, thermophilic, amylolytic, activity